Analisis Peran Guru dalam Mengatasi Kenakalan Siswa di Kelas II Sekolah Dasar Kec. Taraju Kab. Tasikmalaya - Nissa Nurfitri; Cece Rakhmat; Riga Zahara Nurani (PUSTAKA: Jurnal Bahasa dan Pendidikan, 2024)
His research aims to determine the forms of delinquency in class II students at SDN Langensari and SDN Cikubang. The research aims to describe how teachers deal with student delinquency in class II at SDN Langensari and SDN Cikubang. Based on research results, analysis of the role of teachers in dealing with student delinquency in class II of SDN CIKUBANG and SDN Langensari, Taraju subdistrict, Tasikmalaya Regency has been carried out on two teachers and four students. Based on the research results obtained from two teachers and four students, there was mild delinquency among the four people. Mischief such as: fighting, not doing homework, disturbing friends when studying, skipping school. Factors that influence delinquency are family factors, namely disharmony and a broken home (divided parents) and lack of love and attention from parents. There is a description of the results of research conducted by researchers at SDN CIKUBANG and SDN Langensari.